1979
DOI: 10.4319/lo.1979.24.5.0960
|View full text |Cite
|
Sign up to set email alerts
|

Organic carbon export from upland and forested wetland watersheds1

Abstract: Export of organic carbon per unit runoff from five small, eastern North Carolina watersheds with considerable swamp drainage was severalfold higher than the export rates from upland watersheds reported in the literature. This reflects the higher concentrations of organic carbon, especially dissolved forms, in swamp waters and is probably attributable to increased contact time between water and organic debris as well as to concentration effects of high evapotranspiration in swamps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
83
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(92 citation statements)
references
References 6 publications
8
83
1
Order By: Relevance
“…Effect of wetlands on DON-Wetlands are important sources of dissolved organic matter to streams and rivers, particularly when they fringe stream channels or discharge directly into streams (Mulholland and Kuenzler 1979;Eckhardt and Moore 1990;Fiebig et al 1990;Fölster 2000;Raymond and Hopkinson 2003). Shallow flow paths from wetlands to streams bypass most mineral soils, which are known to retain DON as well as DOC (Aitkenhead-Petersen et al 2003).…”
Section: Effect Of Land Use On Don-individual Watershedmentioning
confidence: 99%
See 1 more Smart Citation
“…Effect of wetlands on DON-Wetlands are important sources of dissolved organic matter to streams and rivers, particularly when they fringe stream channels or discharge directly into streams (Mulholland and Kuenzler 1979;Eckhardt and Moore 1990;Fiebig et al 1990;Fölster 2000;Raymond and Hopkinson 2003). Shallow flow paths from wetlands to streams bypass most mineral soils, which are known to retain DON as well as DOC (Aitkenhead-Petersen et al 2003).…”
Section: Effect Of Land Use On Don-individual Watershedmentioning
confidence: 99%
“…Wetlands have been shown to function as sinks for inorganic N through denitrification (Hill, 1996), as well as sites where inorganic N may be converted to organic N (Devito et al, 1989). Although regional studies linking DON to natural landscape features have had limited success (Clair et al, 1994), relationships between stream water dissolved organic carbon (DOC) (Mulholland and Kuenzler 1979;Eckhardt and Moore 1990;Raymond and Hopkinson 2003) and wetland abundance suggest that wetlands may play an important role in hydrologic DON losses from forested and developed watersheds.…”
mentioning
confidence: 99%
“…Peat accumulates due to water-logging, anaerobic conditions and thus slow rates of decomposition. Hydrologie, thermal, and nutrient regimes are the controlling factors of decomposition in wetlands (Moore 1988 Day et al 1977;Mulholland and Kuenzler 1979;McKnight et al 1985;Clair and Freedman 1986;Collier et al 1989;Urban et al 1989: Eckhardt andMoore 1990 …”
Section: Sources Sines and Fluxes Of Docmentioning
confidence: 99%
“…Mulholland and Kuenzler 1979;Mulholland 1981a;Schlesinger and Melack 1981;Grieve 1984a;Moore 1987b: Moore and Jackson 1989: Eckhardt and Moore 1990.…”
Section: Peatlands: An Important Doc Sourcementioning
confidence: 99%
“…The occurrence of mires in boreal headwater catchments has been shown to be significantly correlated with stream chemistry. Processes in peat and other frequently saturated organic soils produce humic substances that are transported to streams (Clair et al, 1994;Dillon and Molot, 1997;Mulholland and Kuenzler, 1979;Eckhardt et al, 1990;Koprivnjak and Moore, 1992;Hope et al, 1994;Mulholland, 1997). Hemond (1990) suggested that the most important processes take place in the riparian zone, and that they depend on stream flow generation.…”
Section: Wetlands Vegetation Cover and Dissolved Organic Mattermentioning
confidence: 99%